A Pilot Study to Examine the Relationship Between Napping and Fatigue in Nurses Practicing on the Night Shift. (November 2017) - Neville, Kathleen; Velmer, Gillian; Brown, Shari; Robol, Nancy
Abstract : OBJECTIVE: The aim of this study is to explore the relationship of night-shift napping on fatigue. BACKGROUND: Nurses' fatigue, especially at night, interferes with quality of life and job performance and impacts safety and health. METHODS: Night-shift nurses completed the Brief Fatigue Inventory and a demographic information sheet to determine differences in fatigue between nurses who napped during their night shift as compared with nurses who did not nap. RESULTS: No statistically significant differences in global fatigue were found; differences in rotating shift, age, and, gender were identified. Rotating shifts, a 2nd job, and caring for family predicted fatigue. CONCLUSIONS: Based on this pilot study, further investigations of fatigue among night-shift nurses are needed as well as evidence-based support to promote sleep.